Analysis of dermoscopic changes of blue nevi on digital follow‐up: A 21‐year retrospective cohort study. (27th March 2023) - Alamon‐Reig, Francesc; Combalia, Marc; Albero‐González, Raquel; Alòs, Llúcia; Carrera, Cristina; Puig‐Butillé, Joan Anton; Villanueva‐Cañas, José Luis; Puig, Susana; Malvehy, Josep; Podlipnik, Sebastian
Abstract: Background: Blue nevi are benign dermal melanocytic proliferations that are often easy to recognize clinically. Rarely, these lesions can display atypical features, suggesting the presence of a malignant blue nevus or mimicking cutaneous metastases of melanoma. Objective: To describe the clinical evolution of blue nevi over time and to assess the need for monitoring these lesions. Methods: We conducted a retrospective cohort study of 103 patients who were followed between December 1998 and November 2019. An artificial intelligence algorithm was used to identify blue nevi from the databases of two digital epiluminescence devices. Changes in the area of each lesion were calculated with a segmentation neural network. Results: We included 123 blue nevi from 103 patients. Most of the lesions segmented, 99 (91.7%), were considered stable. Of the 9 (8.3%) growing blue nevi identified, 2 (1.85%) showed significant growth. The studied growing blue nevi turned out to be cellular blue nevi, presented with a low tumour mutation burden and GNAQ c.626A>T alteration was identified in both lesions. Limitations: Some clinical variants of blue nevi might not be included. Conclusions: Most blue nevi remain stable during their evolution. Rarely, they can show progressive growth, although histopathological or molecular signs of malignancy have not been identified.